Changes in CCN activity of ship exhaust particles induced by fuel sulfur content reduction and wet scrubbing. Issue 1 (30th November 2022) - Santos, Luis F. E. d.; Salo, Kent; Kong, Xiangrui; Noda, Jun; Kristensen, Thomas B.; Ohigashi, Takuji; Thomson, Erik S.
Abstract : Maritime transport remains a large source of airborne pollutants, including exhaust particles that can act as cloud condensation nuclei (CCN). Abstract : Maritime transport remains a large source of airborne pollutants, including exhaust particles that can act as cloud condensation nuclei (CCN). While primary diesel engine exhaust particles are generally considered hydrophobic, international regulations targeting a reduction of particulate emissions from ships may have secondary effects, and therefore influence how exhaust interacts within the atmosphere. The effect of international fuel sulfur content (FSC) regulations on the cloud forming abilities of exhaust particles was investigated using a marine test engine operating on compliant low FSC fuels, non-compliant high FSC distillate fuels and in conjunction with a marine wet scrubber (fresh- and seawater). Particle sizing and liquid droplet activation measurements reveal that compliance measures can have opposing effects on the CCN activity of exhaust particles. For a non-compliant, high FSC fuel, wet scrubbing leads to an increase in CCN activity but not to significant increases in CCN emission factors. However, switching to low FSC fuels resulted in emissions of highly hydrophobic particles, causing a significant reduction in CCN activity resulting in smaller CCN emission factors by at least one order of magnitude. Our observations are supported by chemical analysis of exhaust particles using scanning transmission X-ray microscopy and near edge X-ray absorption fine structure (STXM/NEXAFS) spectra. Potential implications of effects on ship exhaust particles for cloud and climate interactions due to different compliance measures are discussed.